Numerical Simulation and Experimental Verification of Hot Roll Bonding of 7000 Series Aluminum Alloy Laminated Materials - Wei Xu; Chengdong Xia; Chengyuan Ni (Metals, 2024)
In the present study, the hot roll bonding process of 7000 series aluminum alloy laminated materials was numerically simulated and investigated using the finite element method, and the process parameters were experimentally verified by properties testing and microstructure analysis after hot roll bonding. In the roll bonding process of aluminum alloy laminated materials, the effects of the intermediate layer, pass reduction ratio, rolling speed and thickness ratio of component layers were studied. The results of finite element simulations showed that the addition of a 701 intermediate layer in the hot roll bonding process could effectively coordinate the deformation of the 705 layer and 706 layer and prevented the warping of the laminated material during hot rolling. It is recommended to use a multi-pass rolling process with small deformation and high speed, and the recommended rolling reduction ratio is 20%~30%, the hot rolling speed is 1.5~2.5 m/s and the thickness ratio of the 705 layer and 706 layer is about 1:5. Based on the above numerical results, five-layer and seven-layer 7000 series aluminum alloy laminated materials were prepared by the hot roll bonding process. The results showed that metallurgical bonding was realized between each component layer, and no delamination was observed from the tensile fracture between the interfaces of component layers. The tensile strength of the prepared laminated materials decreased with the increase in the thickness ratio of the 705 layer, and the bonding strengths of the laminated materials were in the range of 88–99 MPa. The experimental results verified the rationality of the process parameters recommended by the numerical simulations in terms of warping and delamination prevention.